Diversity and conservation of orchids in San Antonio del Tequendama, Cundinamarca, Colombia - Ordóñez-Blanco, Juan Camilo (2025)
The municipality of San Antonio del Tequendama, Cundinamarca, Colombia, harbours remnants of cloud forests that support a rich diversity of orchids, primarily threatened by habitat loss. This study aims to guide conservation efforts through fieldwork and herbarium records, focused on orchid spatial distribution. The study area covers 82 km², situated at elevations between 1090 and 2700 meters. We conducted 31 field trips between 2017 and 2019. A total of 151 species from 54 genera were documented, offering the most comprehensive list of orchid species recorded in the region, accounting for 3.51% of Colombia’s orchid species. The most diverse genera were Epidendrum (23 spp.), Maxillaria (13 spp.), Stelis (10 spp.), and Cyrtochilum (10 spp.). Thirty genera (19.86%) were represented by only one species. Six threatened species were identified: Cattleya trianae and Masdevallia caudata (Endangered), Pleurothallis mundula, Cyrtochilum ioplocon, Dracula psittacina, and Oncidium gloriosum (Vulnerable). Although the conservation status of some endemic species (26 spp., 17.21%) remains unknown or unassessed, many observed during field trips are rare and vulnerable to illegal collection for commercial purposes. The remaining forests of San Antonio del Tequendama, especially those within protected natural reserves, are crucial for in situ conservation actions at the local level. Our findings on species distribution provide a baseline for assessing the conservation status of orchid populations in cloud forests.